A First Attempt at Modelling Roe Deer (Capreolus capreolus) Distributions Over Europe. (14th July 2014) - Alexander, Neil S; Morley, David; Medlock, Jolyon; Searle, Kate; Wint, William
The presence of roe deer can be an important component within ecological and epidemiological systems contributing to the risk and spread of a range of vector-borne diseases. Deer are important hosts for many vectors, and may therefore serve as a focal point or attractant for vectors or may themselves act as a reservoir for vector-borne disease. Three spatial modelling techniques were used to generate an ensemble model describing the proportion of suitable roe deer habitat within recorded distributions for Europe as identified from diverse sources. The resulting model is therefore an index of presence, which may be useful in supporting the modelling of vector-borne disease across Europe.